2022
DOI: 10.1039/d2nr04053k
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Ni3P/Ni nanoparticles with optimized Ni active sites anchored in N-doped mesoporous nanofibers for boosting pH-universal hydrogen evolution

Abstract: A novel tactic of synergetic electronic coupling is successfully developed for rendering metal-rich phosphides as an efficient pH-universal electrocatalyst for the hydrogen evolution reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 65 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…And their Raman spectra revealed (Figure S9b) that the I D /I G intensity ratio of the Ni 3 P/Ni/VN@NC‐700 sample was 0.986, which was significantly higher than that of Ni 3 P/Ni/VN@NC‐600 (0.655) and Ni 3 P/Ni/VN@NC‐800 (0.696), suggesting that the Ni 3 P/Ni/VN@NC material fabricated at 700 °C was rich in defects within the carbon structure and had a high density of catalytic active sites, and thus promoting the enhancement of the overall catalyst activity. Furthermore, characterization of its microscopic morphological structure (Figure S10) revealed that the microflower's surface of Ni 3 P/Ni/VN@NC‐600 was encapsulated by many blocks and the pores formed by the interlaced nanosheets were also incompletely filled, which may be caused by the incomplete carbonization reaction of the DCD due to the lower heat treatment temperature [48] . With the temperature gradually increasing, Ni 3 P/Ni/VN@NC‐800 presented the microspherical morphology composed of nanoparticle accumulation, and it was evident that the higher heat treatment temperature cannot maintain the microflower‐like structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And their Raman spectra revealed (Figure S9b) that the I D /I G intensity ratio of the Ni 3 P/Ni/VN@NC‐700 sample was 0.986, which was significantly higher than that of Ni 3 P/Ni/VN@NC‐600 (0.655) and Ni 3 P/Ni/VN@NC‐800 (0.696), suggesting that the Ni 3 P/Ni/VN@NC material fabricated at 700 °C was rich in defects within the carbon structure and had a high density of catalytic active sites, and thus promoting the enhancement of the overall catalyst activity. Furthermore, characterization of its microscopic morphological structure (Figure S10) revealed that the microflower's surface of Ni 3 P/Ni/VN@NC‐600 was encapsulated by many blocks and the pores formed by the interlaced nanosheets were also incompletely filled, which may be caused by the incomplete carbonization reaction of the DCD due to the lower heat treatment temperature [48] . With the temperature gradually increasing, Ni 3 P/Ni/VN@NC‐800 presented the microspherical morphology composed of nanoparticle accumulation, and it was evident that the higher heat treatment temperature cannot maintain the microflower‐like structure.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, characterization of its microscopic morphological structure (Figure S10) revealed that the microflower's surface of Ni 3 P/Ni/VN@NC-600 was encapsulated by many blocks and the pores formed by the interlaced nanosheets were also incompletely filled, which may be caused by the incomplete carbonization reaction of the DCD due to the lower heat treatment temperature. [48] With the temperature gradually increasing, Ni 3 P/Ni/VN@NC-800 presented the microspherical morphology composed of nanoparticle accumulation, and it was evident that the higher heat treatment temperature cannot maintain the microflower-like structure. The above results disclosed that the heat treatment temperature played a significant role in the formation of Ni 3 P/Ni/VN@NC hierarchical microflower structure with abundant defects, and the optimum morphology of Ni 3 P/Ni/VN@NC catalyst was achieved when prepared at 700 °C.…”
Section: Synthesis and Characterization Of Ni 3 P/ni/vn@ncmentioning
confidence: 96%
“…They used nickel acetate tetrahydrate/PVA sol–gel for electrospinning, and the obtained nanofibrous hybrid membrane was calcined in an argon atmosphere at 700 °C. Fu reported a novel heterostructured Ni3P/Ni nanoparticle anchored in nitrogen-doped mesoporous carbon nanofibers (Ni 3 P/Ni@N-CNFs) by electrospinning technology and a facile solid-phase calcination protocol . The optimized Ni 3 P/Ni@N-CNF material exhibited outstanding durable catalytic stability, which was primarily attributed to the favorable electronic interactions between Ni 3 P and Ni, increased catalytic active sites, and fast electron/mass transfer rate (Figure b).…”
Section: Overview and Design Of Electrospun Nanofibrous Hybrid Materialsmentioning
confidence: 99%
“…Due to the low loading capacity of metal precursors, the use of metal precursors and polymers to manufacture metal fibers may limit the measurement of their magnetic and electrical properties. Metal/ceramic precursors can overcome these shortcomings and have been widely used in the fabrication of different types of metals, metal oxides, and their carbon composite fibers. The metal/ceramic acetate precursor fiber was first obtained by electrospinning technology, and the composite nanomaterials can be generated after calcination. Barakat et.…”
Section: Overview and Design Of Electrospun Nanofibrous Hybrid Materialsmentioning
confidence: 99%
“…After the mixture was cooled to room temperature, the prepared Ni 3 P sample was treated with 0.5 M H 2 SO 4 for 12 h to obtain its pure Ni 3 P counterpart. 30 Synthesis of Ni 2 P + Ni 3 P. 0.25 g of Ni 2 P and 0.25 g of Ni 3 P were uniformly ground to obtain a physical mixture of Ni 2 P + Ni 3 P.…”
Section: ■ Introductionmentioning
confidence: 99%